Ten-Year Study of Acute Otitis Media in Rochester, NY. Issue 9 (September 2016) - Pichichero, Michael E.
Abstract : This review summarizes a prospective, longitudinal 10-year study in Rochester, NY, involving 760 children where virtually all clinically diagnosed acute otitis media (AOM) was confirmed by bacterial culture of middle ear fluid. This review describes detection of otopathogens in middle ear fluid, nasopharyngeal (NP) otopathogen colonization patterns, AOM risk factor analysis, biomarkers of AOM and antibody responses to NP colonization by otopathogens. After licensure of PCV13, there was an immediate drop in AOM caused by Streptococcus pneumoniae ( Spn ) vaccine serotypes and shortly thereafer an increase in nonvaccine types 16, 21 and 35B. When NP co-colonization occurred, nontypeable Haemophilus influenzae (NT Hi ) predominated over Spn to cause AOM, and NT Hi and Spn both predominated over Moraxella catarrhalis . Transcriptome analysis of peripheral blood mononuclear cells identified unique signatures for NT Hi AOM compared with Spn AOM. Elevation of 3 cytokines in serum (S100A12, intercellular adhesion molecule 1 and interleukin 10) accurately predicted the presence and recovery from AOM and the likely otopathogen. NP colonization was an immunizing event.